Atherothrombogenic Risk Modulation by n-3 Fatty Acids Was not Associated with Changes in Homocysteine in Subjects with Combined Hyperlipidaemia - Grundt, H.; Nilsen, D. W. T.; Hetland, Ø.; Mansoor, M. A.; Aarsland, T.; Woie, L. (Thrombosis and Haemostasis, 1999)
Favourable effects of n-3 fatty acids on the atherogenic risk profile were recently demonstrated in subjects with combined (type IIb) hyperlipidaemia, not responding to a therapeutic diet.Re-examination of a previous patient material was performed to assess the influence of n-3 fatty acids on homocysteine and several coagulation factors.Subjects were randomly allocated to receive either a concentrated compound of 85% eicosapentaenoic acid (EPA)/docosahexaenoic acid (DHA) (n = 28), or corn oil (n = 29), in a daily dose of 4 g for 12 weeks. The intervention was double-blind.Homocysteine remained unchanged in both groups after 12-week treatment. N-3 fatty acids supplementation did not affect the levels of fibrinogen, coagulation factor VII or tissue factor pathway inhibitor (TFPI), while plasminogen activator inhibitor (PAI) increased significantly (Student’s t-test; p <0.05). Total blood platelets were significantly reduced in subjects receiving n-3 fatty acids (Student’s t-test; p <0.05), whereas bleeding times increased non-significantly.